(untitled) (Acta Judicial Journal, 2019)
This article is the final version of the work conducted at the Technical and Procedural Workshops of the Lawyers of the Administration of Justice - Clerks of the Court- held in Comillas in September 2018. It includes the different aspects that the proceedings of entry and registration in an enclosed place under the current Criminal Procedure Law. From its concept and regulation to the material preparation of the documenting record. The numerous problems that these investigative procedures raise to those who intervene in the criminal process - be they legal operators or not - are systematized in independent epigraphs. Giving special attention to those related to the Lawyers of the Administration of Justice; authentic protagonists of some police and judicial investigation proceedings that constitute an inexhaustible source of activity in their Courts of Instruction. I use as an essential instrument to solve the issues raised, the jurisprudence of the Supreme Court - in addition to some doctrinal references-; differentiating such issues according to a constitutional or legal infraction.